Momenty (nie)ciągłości psychologii narracyjnej - Obrębska, Monika; Soroko, Emilia (Człowiek i Społeczeństwo, 2023)
The thematic diversity and the way narrative is understood demonstrate the vitality of the concept and the phenomenon of narrative in psychology. This article presents some questions and dilemmas that narrative psychology, which is still a young discipline in search of its scientific identity, pose to researchers. It is not our ambition to resolve these questions; instead, we perceive them as moments of (dis)continuity in the ongoing narrative story and as markers of the directions of research and theoretical considerations. We identify such themes as the distinction between utterance and narrative, the space between author and listener, the directions in which the notion of narrative identity is expanding, and the link between narrative structure and narrative process. The methodological diversity the narrative perspective introduces allows us to pose research questions in a qualitative and quantitative approach.